Walking Down Memory Lane: Paternalistic Acts of Colonial Cinchona Plantation in Bandung - Alissa Wiranova; Dede Mulyanto; Budiawati Supangkat Iskandar (Endogami: Jurnal Ilmiah Kajian Antropologi, 2025)
This study examines how local residents living near the former Dutch colonial cinchona plantation in Cikembang Village, West Java maintain collective memories of this history through both physical structures and oral traditions. Through ethnohistorical research method, the investigation reveals that local residents' narratives demonstrate a strong connection to the plantation system, largely resulting from the paternalistic labor control practices in the past. The research concludes that these paternalistic relationships served more complex purposes than simply providing basic needs and imposing moral codes—they were deliberately implemented as a strategic mechanism to secure a consistent and dependable plantation workforce over time.